Legal Responsibility of Electronic System Operators for Fraudulent Acts in Marketplace Transactions in Indonesia - Devi Mustika; Lisa Anggraini; Simalango, Juita Octaviani; Agusriansyah Ridwan; Rahmatullah Ayu Hasmiati (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2026)
The rapid expansion of digital marketplaces has intensified concerns over the legal responsibility of Electronic System Operators (ESOs) for fraudulent activities conducted through their platforms. While Indonesia's legal framework recognizes the safe harbor doctrine, it provides limited guidance on the circumstances under which ESOs lose immunity because of inadequate platform governance. This study examines the limits of ESO liability for online fraud and evaluates the relationship between safe harbor protection and due diligence obligations under Indonesian law. Employing normative juridical research through statutory and conceptual approaches, the study analyzes the regulatory framework governing intermediary liability and platform accountability. The findings reveal that safe harbor protection cannot be treated as absolute immunity but is conditional upon the effective implementation of due diligence measures, including user verification, timely responses to reports of unlawful conduct, and proportionate mitigation of foreseeable risks. Building on these findings, this study proposes a Risk-Tiered Intermediary Liability model that calibrates legal responsibility according to the level of platform involvement and the adequacy of preventive measures adopted by ESOs. The proposed framework contributes to intermediary liability scholarship by reconciling innovation-friendly safe harbor protection with accountable digital governance and offers a normative basis for future regulatory reform in Indonesia.